Effect Of Organic And Inorganic Sources Of Nitrogen On Yield Attributes, Grain Yield And Straw Yield Of Rice (Oryza Sativa) - HRUSIKESH PATRO; DEBIPRASAD DASH; DAMODARA PARIDA; PRAMOD KUMAR PANDA; AJAY KUMAR; RAMESH C. TIWARI; MOHAMMAD SHAHID (International Journal of Pharma and Bio Sciences, 2011)
The present investigation entitled, “Effect of organic and inorganic sources of nitrogen(N) on yield attributes and yield of rice (Oryza sativa)” was carried out at the Agricultural Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi during Kharif seasons of 2001 and 2002, in agro–ecological zone V of India. The soil of experimental site was sandy clay loam in texture with normal pH, low in nitrogen and phosphorus and medium in organic carbon and potassium contents. The experiment was laid out in Randomised Block Design with nine treatments replicated thrice. The treatments were applied to rice crop during kharif season. Application of 120 kg N ha-1 through chemical fertilizer (T9) and combination of D.S, P.M and C.W (T8) increased effective tillers m-2 as well as HI significantly as against the other N sources along with control (T1) and remained at par to each other. However, highest number of effective tillers m-2, filled grains per panicle, 1000 grain test weight and HI were observed in the treatment receiving recommended doses of chemical fertilizer (T9) followed by the treatment T8 (@ 40 kg N ha-1 each source). Application of N through chemical fertilizer (T9) brought about significant improvement in grain and straw yields of rice crop and established superiority over rest of the treatments. Among organic N sources, supplication of N through combination of D.S + P.M + C.W @ 40 kg N ha-1each (T8) increased the grain and straw yield significantly as against the application of rest of the organic N sources and the control (T1) except the straw yield due to incorporation of P.M alone (T3) which remained at par.